THE ISSUE OF VOICE ADJUSTING IN UZBEK TRADITIONAL SINGING, THE IMPORTANCE OF THE TEACHER IN THE DEVELOPMENT OF THE STUDENT, AND RECOMMENDATIONS ON REPERTOIRE - Suhrob Jumayev (Modern American Journals, 2025)
The article examines issues related to vocal skills in Uzbek traditional singing, talks about the enunciation of letters and the possibility of performance. The term “Namud” is defined. As an example, voice adjusting exercises are given. An analysis of a ghazal is presented. To a certain extent, the issue of repertoire is considered and the role of the teacher in the development of the student is analyzed. The names of some terms were written in Uzbek spelling.
Keywords: Avj, culmination, enunciation, maqom, ensemble, tenor, namud, voice adjusting exercises, staccato, the text of the piece, ghazal, listener, manzuma, repertoire.